Gudjonsson Suggestibility Scale-2 Turkish reliability and validity study - Özcan, Ezgi Ildırım; Ziyalar, Neylan (The Bulletin of Legal Medicine, 2023)
Objective: This paper aims to adapt Gudjonsson Suggestibility Scale-2 (GSS-2) which is  objective measurement for measuring individuals susceptibility to interrogative suggestibility into Turkish.Methods: Form is applied to 175 people participated whose age ranged from 19 to 36. GSS-2 applied to participants by the researchers. In GSS-2 a story regarding to bicycle accident read to the participants. Participants also filled the Dissociative Experiences Scale, Submissive Act Scale, and Cognitive Failure Questionnaire for construct validity.Results: Descriptive analysis result showed that mean values for immediate recall of the correct information, mean of the immediate recall average of the confabulation, the correct information mean for delayed recall, the mean of the confabulation in the delayed recall are 14,99; 3,23; 14,42; 4,03 respectively. For suggestibility scores mean scores are found to be 5,25 for yield 1 score; 6,66 for yield 2 score; 4.1 for shift score and the mean score for the total suggestibility is 9,35. The cronbach alpha values ​​of the subscales of the scale were calculated .713 for yield 1,  .812 for yield 2, .600 for shift score. Confirmatory factor analysis failed that yield 1 factor  found to be unidimensional in accordance with the original, however, shift factor did not show unidimensional properties, that some questions did not fit factor structure. Conclusion: The study results suggest that culture and language factors may be effective in witness memory and suggestibility. There is need for further studies regarding to Turkish form of GSS-2.
Keywords: Gudjosson Suggestibility Scale; eyewitness testimony; eyewitness memory; suggestibility